2018
DOI: 10.3390/educsci8030133
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Free Time Satisfaction and Stress Levels of Elite-Level Student-Wrestlers

Abstract: The purpose of this research was to examine the relationship between free time satisfaction and stress levels of elite level student wrestlers according to some demographic factors. The sample of the study consisted of 119 (85 male and 34 female) elite level student wrestlers who participated in the Wrestling National Team camp in 2018. As data collection tools, “Personal Information Form”, “Stress Scale in Working Life: SSWL”, and “Free Time Satisfaction Scale: FTSS” were used. In the analysis of the derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…In this sense, leisure satisfaction levels did not differ by being single or married. In light of the findings, the findings of Ngai (2005), Koç and Er (2020), and Yaşartürk et al (2018) were in line with the results of the current study. It can be suggested that marital status is not an influential variable in determining leisure satisfaction.…”
Section: Discussionsupporting
confidence: 91%
“…In this sense, leisure satisfaction levels did not differ by being single or married. In light of the findings, the findings of Ngai (2005), Koç and Er (2020), and Yaşartürk et al (2018) were in line with the results of the current study. It can be suggested that marital status is not an influential variable in determining leisure satisfaction.…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, there are also studies indicating that men have higher academic self-efficacy levels than women (Durdukoca, 2010;Vurucu, 2010). However, there are also studies in the literature that did not find significant differences between male and female students (Doğaner, 2017;Kavrayıcı & Bayrak, 2016;Kılıç & Öncü, 2014;Özsüer, 2011;Uysal, 2013;Ünlü & Kalemoğlu, 2011;Yaşartürk et al, 2018). This shows that the studies in the literature show different results and that the female students in our sample group had higher self-confidence in their courses or academic studies, and it can be concluded that women, in the social conditions they live in, are more effective than males in learning and in applying their acquisitions in real life in terms of the social dimension.…”
Section: Discussionmentioning
confidence: 99%
“…The first is to apply a Light Gradient Boosting Machine (LightGBM) model and the SHapley Additive exPlanation (SHAP) approach based on game theory to analyze the factors influencing leisure time from the standpoint of the nonlinear relationship. The extant literature is primarily based on linear models [14] and lacks the exploration of nonlinear relationships. Second, we conduct thorough data analysis on primary survey data collected in 2011, 2016, and 2021, while most of the previous studies used secondary data.…”
Section: Introductionmentioning
confidence: 99%
“…Second, we conduct thorough data analysis on primary survey data collected in 2011, 2016, and 2021, while most of the previous studies used secondary data. Third, as far as we know, this paper is the first to study the changes in leisure time based on time allocation, demographics, occupation, and family characteristics, as compared to previous research that explored the correlation between a specific factor and leisure time [3,14,15]. Last but not least, based on the conclusions of this paper, we discuss feasible measures to increase and make full use of personal leisure time from three aspects: government policy system, market product supply, and personal leisure demand.…”
Section: Introductionmentioning
confidence: 99%